Chránění generátoru při nesymetrickém zatížení - Kuba, Petr (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2009)
Tato práce se zabývá problematikou nesymetrického zatížení generátorů a ochranou při tomto abnormálním provozním stavu. V úvodu je popsáno, proč je důležité se touto problematikou zabývat. Teoretická část práce rozebírá postup při řešení nesymetrických stavů pomocí metody souměrných složek. Jsou popsány příčiny jejich vzniku, možnosti zmírnění a hlavně vliv zpětné složky proudu, vzniklé při nesymetrickém zatížení, na generátor a jeho jednotlivé části. Ke konci této části je popsán princip ochrany při nesymetrii generátoru. Praktická část se zabývá metodikou pro nastavení a testování ochrany. Použitá ochrana je součástí terminálu točivého stroje REM 543 od společnosti ABB. Pro testování ochrany bylo využito testovací zařízení elektrických ochran TZO3 od společnosti EGÚ Brno. V závěru práce jsou shrnuty nejpodstatnější informace a výsledky měření.

The thesis deals with the problem of unbalance in generators and discusses various means of generator protection against the effects caused by this abnormal working condition. The general importance of the problem is described in the introductory part of this work. The theoretical section of the thesis contains an analysis of procedures applied to solve different types of unbalance by the help of the method of symmetrical components. As a central aspect of the topic, the causes of unbalance are examined. This investigation is realized together with a close insight into the diverse possibilities of unbalance reduction and, importantly, in respect the effects of negative sequence current on a generator and its components. The principles of generator protection against unbalance are described at the end of this section. In its practical part, this work deals with the procedure of protection setting and testing. The applied protection is an actual component of the REM 543 machine terminal as made by the ABB company. In order to facilitate the testing of the protection, we used the TZO3 electrical protection testing device provided by the EGÚ Brno, a. s. company. A summary of the most important information and measurement results can be found in the final part of the thesis.
Protection for Generator Unbalance
Keywords: Abnormální provozní stav; ochrana; metoda souměrných složek; zpětná složka; testovací zařízení.; Abnormal working condition; protection; method of symmetrical components; negative-phase-sequence; testing device.